2016
DOI: 10.20450/mjcce.2016.919
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, physicochemical characterization and antibacterial activity of novel (benzoylamino)methyl derivatives of quinolones

Abstract: Herein we report the synthesis of different derivatives of (fluoro)quinolones norfloxacin, ciprofloxacin and pipemidic acid, by incorporating (benzoylamino)methyl on the free nitrogen of the pyperazinyl moiety. The compounds were structurally characterized by 1D and 2D NMR, FTIR and highresolution mass spectroscopy. In addition, their physicochemical properties were a matter of interest to be correlated with their structure and antimicrobial activity in vitro. Their antimicrobial activities were screened again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A previous correlation study reported that passive diffusion is not the defining mechanism for fluoroquinolone entry to bacterial cells minimizing the role of lipophilicity as observed in the current study. 18 Similarly, heat of formation and Gibbs energy showed weak correlations with the activity against S. aureus, whereas they showed weak or no impact on the activity against different gram-negative strains. Change in Gibbs free energy is usually negative, indicating that the complex formation between a compound and target enzyme is spontaneous.…”
Section: Calculation Of Lipophilicity Polarizability and Topology Pmentioning
confidence: 98%
“…A previous correlation study reported that passive diffusion is not the defining mechanism for fluoroquinolone entry to bacterial cells minimizing the role of lipophilicity as observed in the current study. 18 Similarly, heat of formation and Gibbs energy showed weak correlations with the activity against S. aureus, whereas they showed weak or no impact on the activity against different gram-negative strains. Change in Gibbs free energy is usually negative, indicating that the complex formation between a compound and target enzyme is spontaneous.…”
Section: Calculation Of Lipophilicity Polarizability and Topology Pmentioning
confidence: 98%
“…[3] The chemical shifts and coupling constants of the fluoro-quinolone-piperazinyl moiety of ciprofloxacin and its derivatives showed very close values indicating that the benzamidomethyl substituents do not change the stereochemical behaviour and electronic structure of the parent compound. [3] Any information about the structure of these widely used antibiotics would be essential for a complete understanding of their biological activity. Due to the Correction added on 18 March 2019, after first online publication: A prefix 'S' has been added to the pagination of this article, so the page range has changed from 75-84 to S75-S84.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, a series of derivatives of ciprofloxacin with novel benzamidomethyl substituents at N4′ of the piperazine ring have been synthesized as potential prodrugs with higher lipophilicity than the leading compound, and their structures were characterized with the help of 1D and 2D NMR spectra . The chemical shifts and coupling constants of the fluoro‐quinolone‐piperazinyl moiety of ciprofloxacin and its derivatives showed very close values indicating that the benzamidomethyl substituents do not change the stereochemical behaviour and electronic structure of the parent compound …”
Section: Introductionmentioning
confidence: 99%